Implementasi Sistem Pengendalian Internal Pemerintah untuk Mengukur Kinerja Keuangan Badan Pendapatan Daerah di Kota Malang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the impact of the implementation of the Government Internal Control Sistem (SPIP) on financial performance at the Regional Revenue Agency (Bapenda) of Malang City from 2022 to 2024. SPIP consists of five key components: control environment, risk assessment, control activities, information and communication, and monitoring. Financial performance is measured using indicators from the Government Institution Performance Accountability Sistem (SAKIP), which reflects how well the government institution achieves its financial goals and objectives. This study uses a quantitative approach with an explanatory method, where data was collected through a questionnaire distributed to 34 Bapenda employees in Malang City. The collected data was then analyzed using SPSS version 25 to examine the relationship between SPIP implementation and financial performance. The results indicate that four of the five SPIP components, namely risk assessment, control activities, information and communication, and monitoring, have a positive and significant impact on financial performance. This means that the better the implementation of these components, the better the financial performance achieved by Bapenda Malang City. However, the control environment component does not significantly affect financial performance. This suggests that while the control environment is important, other factors such as operational control and communication play a more dominant role in supporting financial performance. Based on these findings, several recommendations for Bapenda Malang City include strengthening SPIP implementation by conducting regular coaching and outreach programs. Additionally, it is recommended to hold workshops with all work units, provide technical training to develop dashboards, and establish clear Standard Operating Procedures (SOPs) and flowcharts. Setting up a schedule for SOP publication and routine briefings, as well as developing performance indicators and quarterly evaluation checklists, is expected to enhance SPIP implementation and strengthen financial accountability at Bapenda Malang City.